2013
DOI: 10.7314/apjcp.2013.14.10.6085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PSA and DRE on Histologic Findings at Prostate Biopsy in Turkish Men Over 75 Years of Age

Abstract: Prostate specidic antigen (PSA) and digital rectal examination (DRE) are the known predictive factors for positive prostate biopsies differing according to the age, region and race. There have been only very limited studies about the impact of PSA on histological findings at prostate biopsy in Turkey. The aim of this study was to evaluate the impact of PSA and clinical stage on histologic findings of prostate biopsy in men older than 75 years of age as a first study in the Turkish population. A total of 1,645 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A 50 years old American man has a lifetime risk of 40% for latent cancer, 16% for developing clinically apparent cancer and a 2.9% risk of death due to prostate cancer. Other factors including widespread use of prostate specific antigen (PSA) screening also appear to have contributed to the increase in annual prostate cancer incidence (Verim et al, 2013). PSA is a glycoprotein produced by cell, either benign or malignant of the prostate gland.…”
Section: Introductionmentioning
confidence: 99%
“…A 50 years old American man has a lifetime risk of 40% for latent cancer, 16% for developing clinically apparent cancer and a 2.9% risk of death due to prostate cancer. Other factors including widespread use of prostate specific antigen (PSA) screening also appear to have contributed to the increase in annual prostate cancer incidence (Verim et al, 2013). PSA is a glycoprotein produced by cell, either benign or malignant of the prostate gland.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the proportion of men with severe LUTS was significantly lower in men detected with prostate cancer during screening than in those without cancer, suggesting the possible existence of men with LUTS who underwent PSA testing outside the population screening program. Previous studies revealed that benign prostatic hyperplasia (BPH) affected serum PSA levels, and elevated serum PSA levels could be a proxy parameter of prostate volume in patients with BPH (Hochberg et al, 2000;Mochtar et al, 2003;Verim L et al, 2013). Considering this consensus, serum PSA levels may be higher in men with LUTS than in those without LUTS in the entire population, a possibility addressed in several studies (Matsubara et al, 2006;Franlund et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PSA screening is controversial, and PSA levels may also be high due to presence of BPH, infection or by manipulation of the prostate gland by surgery or catheterization (Svetec and Thompson, 1998). Using histopathological procedure for prostate cancer diagnosis, pathologists obtain tissue samples from prostate biopsies and examine it after staining protocols to identify the tissue structures (Orozco et al, 1998;Verim et al, 2013). This traditional histopathological-based diagnosis has remained the standard diagnostic method for many years but with the introduction of advanced techniques like microarrays, mass spectrometry and DNA sequencing, new avenues have opened in cancer diagnosis and therapeutics.…”
Section: Introductionmentioning
confidence: 99%